2015
DOI: 10.5535/arm.2015.39.6.964
|View full text |Cite
|
Sign up to set email alerts
|

Care Status of the ALS Patients With Long-Term Use of Tracheostomy Tube

Abstract: ObjectiveTo evaluate the care status of the amyotrophic lateral sclerosis (ALS) patients with long-term use of tracheostomy tube by caregivers of ALS patients.MethodsA survey was conducted in the form of questionnaires to ALS patients and their caregivers. All measurements were performed by two visiting nurses. For statistical analysis, SPSS ver. 22.0 and Mann-Whitney U test on non-normal distribution were used.ResultsIn total, 19 patients (15 males and 4 females) and their caregivers participated in the surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…Ventilation practices and techniques vary from one subject to another with few consequences on TA except the use of cuffed tracheostomy tube that is significantly associated with P. aeruginosa colonization of the respiratory tract. A survey conducted by Park et al in Korea in amyotrophic lateral sclerosis patients with long-term use of tracheostomy tube showed that almost all the patients and caregivers had an erroneous idea about cuff volume and pressure [18]. P. aeruginosa colonization may be due to retention of secretions up to the cuff even though in our study, most of the cuffed tracheostomy tubes are deflated.…”
Section: Discussionmentioning
confidence: 59%
“…Ventilation practices and techniques vary from one subject to another with few consequences on TA except the use of cuffed tracheostomy tube that is significantly associated with P. aeruginosa colonization of the respiratory tract. A survey conducted by Park et al in Korea in amyotrophic lateral sclerosis patients with long-term use of tracheostomy tube showed that almost all the patients and caregivers had an erroneous idea about cuff volume and pressure [18]. P. aeruginosa colonization may be due to retention of secretions up to the cuff even though in our study, most of the cuffed tracheostomy tubes are deflated.…”
Section: Discussionmentioning
confidence: 59%
“…ALS leads to weakness and atrophy of the oropharyngeal and respiratory muscles, triggering dysphagia and respiratory failure, the main causes of death in ALS patients. Respiratory failure usually has a late onset, so most patients are assisted by NIV or undergo tracheostomy to improve and prolong life 19 . Dysphagia, in turn, can cause choking, dehydration, malnutrition and weight loss, making gastrostomy one of the main procedures used for the symptomatic treatment of this condition 20 .…”
Section: Variablesmentioning
confidence: 99%
“…Therefore, attempts have been made to obtain a low-pressure, high-volume endotracheal tube cuff for several years. The ideal cuff inflation pressure minimizing the risk of both tracheal wall injury and aspiration has been known to be approximately 20–30 cmH 2 O [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%